(untitled) (Medico Legal Update, 2021)
Bullying can take many forms, one of which is verbal bullying in the form of reproach, slander, cruel criticism, personal or racial insults. This study aims to examine the incidence of verbal bullying that occurs in early adolescents at Pallangga 5 Junior High School and Sungguminasa 3 Junior High School, Gowa Regency. This research uses a qualitative case study approach. Data was obtained through Focus Group Discussion (FGD), in-depth interviews with 59 informants and document review. Content analysis is used to identify topics or categories in the data. The results showed that the forms of verbal bullying varied, ranging from harassing, threatening, using verbal abuse by making fun of parents and the name of the victim. Therefore, schools should intensify the activities of the ambassador team so that verbal bullying can be minimized and teachers need to add insight into verbal bullying.